The power preparation of sportsmen and its communication with the efficiency of the training process. - Ahmetov R.F; Romanchuk V.N; Prontenko K.V; Boyarchuk A.M (Kharkov National Pedagogical University, 2010)
The research of power qualities of sportsmen in weightlifting with a different qualification - the pupils of child-youth sporting schools of Zhytomyr region (19-23; CMS, MS; n=21) in the four groups of gravimetric categories, the comparison of finding data with the indexes of sportsmen of other regions of Ukraine, the correlation analysis of indexes of sportsmen in power exercises and their sporting results are being are considered in the article. It is definite, that for the rise of level of sporting trade, power qualities must be perfected to the athletes in categories 60 - 75 kg, and in categories 80, 90 and more than 90 kg the requirements to development of power go down.